Correlation between Students’ Cognitive Reading Strategies and Reading Comprehension - Edi Wahyono (Jurnal Studi Guru dan Pembelajaran, 2019)
This research aims to 1) describe students’ responses toward cognitive reading strategies and their reading comprehension score; 2) find out the correlation between students’ cognitive reading strategies and their reading comprehension. The current research is quantitative in nature. The quantitative is intended to describe the responses of students to cognitive and reading strategies and to explain to what extent the correlation between students’ cognitive reading strategies and reading comprehension. The samples are the fourth semester students of English education as subjects or participants of the research. Data were collected by distributing questionnaires to get responses from students in term of Cognitive Reading Strategies. IELTS Reading Testing was used to get Students’ reading comprehension scores. The quantitative data were analyzed by correlation product moment. The results of the study shows that most of students usually use four cognitive reading strategies included in this research and cognitive reading strategies correlate significantly to students’ reading comprehension with p value of 0.00 and coefficient value of 0.61.